Financování pořízení dlouhodobého majetku v obchodní společnosti - Ekrt, Nicole (Vysoké učení technické v Brně. Fakulta podnikatelská, 2013)
Bakalářská práce se zaměřuje na různé formy financování dlouhodobého majetku. Informuje o finanční situaci obchodní společnosti, a možnostech financování nového pořizovaného dlouhodobého majetku (tahač). Porovnává nabídky úvěrů a leasingů od vybraných bankovních institucí a leasingových společností. Závěrem vyhodnotí nejefektivnější formu financování.

The bachelor´s work is specialized on different forms of financing of long-term property. It informs about financial situation of business company and possibility of financing of newly bought long-term property (truck). It compares the forms of financng, the credit and the leasing offered from selected bank institutions and leasing companies. Eventually considers the most effective way of financing.
Financing Purchase of Long-Term Property in the Company
Keywords: Dlouhodobý majetek; financování; obchodní společnost; vlastní kapitál; cizí kapitál; leasing; bankovní úvěr; zadluženost; rentabilita; likvidita.; Long-term property; financing; bussines company; registered capital; other sources; leasing; banking loans; debt; profit ratio; liquidity.